2008
DOI: 10.3998/tia.17063888.0026.020
|View full text |Cite
|
Sign up to set email alerts
|

16: A Research–Based Rubric for Developing Statements of Teaching Philosophy

Abstract: Despite itsubiquity asthewaythat instructors represent their views on teaching andlearning, the statement ofteaching philosophy can be afrustrating document to write and theresults are often uneven. This chapter describes a rubric created at the University ofMichigan's Center for Research on Learning and Teaching to help faculty andgraduate students craft teaching statements. We describe theresearch thatinformed thecreation of therubric, talk about howweuse the rubric in ourconsultations andworkshops, andprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Our study, focusing specifi cally on individuals from the fi eld of TESL, found some commonalities in terms of TPs' primary topics with previous research. An important way in which our fi ndings and previous research align pertains to the discussion of Teaching approaches (e.g., Teaching methods and evaluations in Schönwe er et al [2002] and Enactment of Goals in Kaplan et al [2008]). Clearly, this dimension is of utmost importance if a TP is to convey to the reader what the teacher does in the classroom.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Our study, focusing specifi cally on individuals from the fi eld of TESL, found some commonalities in terms of TPs' primary topics with previous research. An important way in which our fi ndings and previous research align pertains to the discussion of Teaching approaches (e.g., Teaching methods and evaluations in Schönwe er et al [2002] and Enactment of Goals in Kaplan et al [2008]). Clearly, this dimension is of utmost importance if a TP is to convey to the reader what the teacher does in the classroom.…”
Section: Discussionmentioning
confidence: 71%
“…Finally, across the two contexts, we found that TPs accounted for learners from diverse backgrounds. Kaplan et al (2008) propose several guiding questions to promote this type of refl ection. Schönwe er et al ( 2002) are less explicit but still include language that requires a discussion of learners' characteristics and how these interact with the learning environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of citizens fully conscious of their role, of their responsibilities and the stakes these represent, is an asset in face of challenges that arise. Nevertheless, requests for teaching philosophies are becoming more and more frequent in the academic market and amongst tenure and promotion committees (Bruff, 2007;Kaplan et al, 2008;and Meizlish & Kaplan, 2008).…”
mentioning
confidence: 99%